Kebijakan Pendidikan Era Orde Lama Dan Pengaruhnya Terhadap Pendidikan Islam: EDUCATION POLICY OF THE OLD ORDER ERA AND ITS INFLUENCE ON ISLAMIC EDUCATION - Anggita, Lonie; Khoiri, Qolbi (Innovative: Journal Of Social Science Research, 2025)
This research aims to determine the educational policies implemented by the Old Order government and their impact on Islamic education in Indonesia. The focus of this research is to understand in depth the Old Order government, the educational policies implemented, and the influence of these policies on Islamic education in the country. During the Old Order, there were efforts to fight for reform in Islamic education, marked by the issuance of a number of policies aimed at improving the quality of Islamic education, including the implementation of the Compulsory Madrasah Learning (MBW) program. Indonesia achieved independence from colonialism. The Netherlands on August 17, 1945. The period of President Soekarno's leadership, which lasted from 1945 to 1966, was known as the Old Order, which was different from the subsequent era led by President Soeharto. Government policy during this period paid special attention to Islamic boarding schools and madrasas, which started when the Central Indonesian National Committee Working Body (BP KNIP) submitted recommendations to the government on December 27 1945. This research aims to examine the concept of government in that era and its impact on education in Indonesia. The method used in this research is a basic theory method which is based on data collection through literature study, where the author reads and analyzes books or literature related to the issue under study. Although there are positive and negative sides to the policies issued, the development of madrasas can be considered a significant effort by Islamic education to maintain its existence and identity, while adapting to changing times.